MENGENALI KEARIFAN LOKAL RUMAH VERNAKULAR MELALUI BENTUK DAN BAHAN BANGUNAN PADA RUMAH DI KUALA TRIPA, ACEH - Nursaniah, Cut; Izziah; Laila Qadri (Jurnal Koridor, 2018)
Infrastructure development, both buildings and roads, often result in changes in the surface condition of the landscape and lead to calamity. As happened in the residential area of ​​the watershed Kuala Tripa, Aceh, lately kept flooded. The house is constructed on the ground ignores environmental character and threaten the sustainability of neighborhoods Kuala Tripa in the long term. Kuala Tripa form of physical environment is swamp, major rivers, and estuaries. Settlement of Kuala Tripa has a vernacular house that shows harmony and conformity with the environment. The occupancy adaptations can be identified by the shape and material of construction. Studies using qualitative descriptive methods to find local wisdom in the form and vernacular house building materials to be adapted and applied to the current construction. The results of the study on people's understanding of the architecture and building construction, the use of local building materials and the introduction of the local environment indicates that the potential of the vernacular architecture of Kuala Tripa can be used for residential development of the present and the future. Values ​​in local wisdom and technology skills through shape and material the Kuala Tripa vernacular house building can be used as the basis for the development of the built environment today so adaptive to the environment and respond to disasters.